Design and analysis of 1D photonic crystal doped with magnetized cold plasma defect for application of single/multi-channel tunable narrowband filter. (1st June 2022) - Panda, Abinash; Pukhrambam, Puspa Devi
Abstract: The present research demonstrates the tunable filtering properties of a single/multi-channel filter based on 1D photonic crystal (PhC), which is designed with dielectric materials (A, B) and magnetized cold plasma (P). The proposed filter has a configuration of A / B M A / P / B N ( A / B ) M . Transmission spectra of the structure is investigated for both right-hand polarization and left-hand polarization configurations of the plasma material by employing the well-known transfer matrix method. It is found that number of periods of the plasma layer (N) decides the single-channel and multi-channel operations of the filter. It is revealed that the external magnetic field can be manipulated to tune the frequency of the filter. Also, it is found that the geometrical parameters such as thickness of the plasma layer, plasma density, and incident angle play a significant role in tuning the defect mode frequency. Moreover, the color map plot is studied to provide a clear insight of shifting nature of the defect mode frequency. Quality factor of the filter is evaluated vis-à-vis different geometrical parameters. Our considered structure can be the mainstay for filtering applications in microwave regions, and can find suitable applications in dense wavelength division multiplexing and high speed signal processing.